ApoB/ApoA-1 Ratio as a Novel Prognostic Predictor in Patients With Primary Small Cell Carcinoma of the Esophagus - Chen, Hao; Chu, Ling-Yu; Li, Xiao-Hui; Peng, Yu-Hui; Liu, Can-Tong; Tian, Li-Ru; Xie, Jian-Jun; Xu, Yi-Wei (Frontiers in Oncology, 2020)
Background and Aim: Primary small cell carcinoma of the esophagus (SCCE) is a rarely aggressive disease characterized by rapid progression, widespread metastasis and poor prognosis. This study was aimed to evaluate the prognostic significance of serum lipids for overall survival (OS) in SCCE patients. Methods: We retrospectively analyzed SCCE patients in a training cohort (61 patients) and validated them in a validation cohort (27 patients). These cases were collected from Sun Yat-sen University Cancer Center from 2006 to 2017. Univariate and multivariate Cox survival analyses were performed to determine serum lipids as prognostic factors associated with the patient's OS. Time-dependent receiver operating characteristics (ROC) were used to compare predictive power of independent prognostic factors. The predictive accuracy and discriminative ability of the prognostic factors were measured by the concordance index (C-index) and decision curve, and were compared with the TNM stage system. Results: On multivariate analysis of the training cohort, independent factors for survival were gender, BAR (ApoB/ApoA-1) and TNM stage. The area under the curve (AUC) of BAR+TNM stage in the training cohort was higher than that of TNM stage for OS, and similar result was observed in the validation cohort. The c-index of BAR+TNM stage for predicting the OS was 0.655 (95% CI = 0.571–0.740), which was higher than that of TNM stage (0.614 (95% CI = 0.530–0.698)) in the training cohort. In the validation cohort, the C-index of the BAR+TNM stage for predicting OS was also higher than that of the TNM stage (0.688 (95% CI: 0.570~0.806) vs. (0.512; 95% CI: 0.392~0.632)). In addition, decision curve analysis also showed that the predictive accuracy of BAR+TNM stage for OS was higher than TNM stage both in the training and the validation cohorts. Conclusions: BAR represents a promising prognostic indicator that might complement TNM stage in the prognosis of SCCE, and that warrant further assessment in large SCCE patient cohort.